Effect of high-quality nursing interventions on the quality of life and cardiac index in acute coronary syndrome patients treated with drug-eluting stents: a randomized trial study - Zeinab Abdollahifar; Mahdi Karimyar Jahromi; Khatereh Dehghani; Mohammad Ali Montaseri (BMC Nursing)
Abstract Background Nursing care is important and necessary for Acute Coronary Syndrome patients who have undergone angiography and stenting, to minimize complications. The purpose of this study was to assess the effects of High-Quality Nursing Interventions on the quality of life and cardiac index of Acute Coronary Syndrome patients, treated with drug-eluting stents. Methods In this randomized trial, 70 patients of the cardiac intensive care units in one of Jahrom university of medical sciences hospitals (Iran) were selected from July 2023 to October 2023 by the available method, and randomly allocated (stochastic assignment) to two intervention (High-Quality Nursing Interventions) and control groups (routine nursing care). Quality of life and Cardiac Index were measured by cardiac index calculation formula and the McNew Cardiac Quality Questionnaire, respectively. Data were analysed using SPSS version 19 software, Mann‒Whitney, chi‒square and Wilcoxon tests, with a significance level at a p < .05. Results A statistically significant difference demonstrated between the mean of the quality of life and cardiac index in the intervention group(p < .05). Conclusions High-Quality Nursing Interventions improved quality of life and cardiac index of Acute Coronary Syndrome patients, treated with drug-eluting stents. Therefore, it is recommended to use this nursing approach in special cardiac care units. Trial registration IRCT79432(2024.10.08), “Retrospectively registered”.